Анализ нелинейного взаимодействия изгибных форм композитных цилиндрических оболочек, заполненных жидкостью - Ковальчук, П.С.; Крук, Л.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The problem of the particularities of a multimode nonlinear deformation of the orthotropic cylindrical shells filled by a liquid on their free vibrations is considered. The main attention is paid to the analysis of the interaction of different forms (the modes) of a carrying shell on the realization of internal resonances.